The Marketing Efficiency Development to Create Value-Added for Product and Service of Community-Based Tourism. Study Case for Phatthalung Province - NA SONGKHLA, Ratirath; WANVIJIT, Wit; CHAROENBOON, Pawintana; NINAROON, Panida (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021DO - 10.14505//jemt.v12.1(49).23, 2021)
This study aims to examine the hypothesis and to carry out the path analysis of casual relationship influencing the marketing efficiency development to create value-added for product and service of community-based tourism; Phatthalung Province, Thailand. The findings are as follows. First, the hypothesis model matched with the empirical data by considering the value of CMIN/df = 1.596, p-value = .768, GFI = .976, AGFI = 0.972. RMR = 0.000, RMSEA = 0.005, NFI = 0.991, TLI = 0.998 and CFI = 0.999, respectively. The total effect of the causal variable having most effect towards the marketing efficiency development is the entrepreneurial orientation and all compositions explained the marketing efficiency’ s variance accounting for 71.90%. Second, the conceptual model of the causal relationship having effect towards the marketing efficiency development consists of one direct effect variable – the entrepreneurial orientation whereas there are 3 direct and indirect effect variables having effect towards the marketing competency; risk appetite, proactive operation and innovation capability.